Correlates of intimate relationship satisfaction among investigators of child sexual abuse material - Gewirtz-Meydan, Ateret; O'Brien, Jennifer E.; Mitchell, Kimberly J. (Frontiers in Public Health, 2023)
This study investigates correlates of intimate relationship satisfaction among investigators of child sexual abuse material (CSAM). Previous research has shown that exposure to CSAM content can negatively impact investigators' emotional well-being, but little is known about its association with their intimate relationships. The study included 500 participants who were police investigators, forensic examiners, and other professionals connected with the criminal justice system in the United States that are exposed to CSAM as part of their profession.The study collected data through an anonymous survey administered via the Qualtrics online survey system. The findings reveal that higher levels of depressive symptoms and post-traumatic stress disorder are associated with lower relationship satisfaction among CSAM investigators.Additionally, group connectedness is positively related to relationship satisfaction for both men and women. Parent investigators also reported lower relationship satisfaction, suggesting unique challenges faced by this subgroup. Exposure to varying types of CSAM content was not significantly related to lower relationship satisfaction. This study highlights the association between depressive symptoms and PTSD with relationship satisfaction among CSAM investigators, emphasizing the role of group connectedness in promoting positive outcomes for both male and female investigators. Recognizing the association between depressive symptoms and PTSD with relationship satisfaction can guide interventions and support services for investigators, promoting group connectedness and addressing mental health concerns to enhance resilience and effectiveness in combating child exploitation.